DIMENSI IDENTITAS PENULIS IRLANDIA JOHN MILLINGTON SYNGE - Manangkabo, Junaidi Sutomo (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This skripsi entitled ?Dimensi Identitas Penulis Irlandia Bernama John Millington Synge? aims at discussing the identity dimensions John Millington Synge has. In analyzing, a theory on identity dimensions by Wallace, Levy Strauss, and Miller in Honigmann Handbook is applied. In this theory, the identity dimensions compriseNationality, Education, Ecology, and aspects of  Literature dimensions. In data analysis, ?a content analysis? is applied andthen classified in to the above mentioned four dimensions. The collected data is analyzed descriptively using both approaches, extrinsically, and intrinsically. Extrinsically, the focus is on the concepts of anthropology namely identity. Intrinsically, the attention falls on the aspects of literature namely plot, character, setting, theme, and point of view. The findings show that John Millington Synge is evidently covers four dimensions in his life either individually or personally.   Keywords: Identity, Dimensions, Individual, Personal